Validation of Malayalam Translation of the Sydney Swallow Questionnaire (MSSQ): A Prospective Cross-Sectional Study - Narasimhan, Srirangam Vijayakumar; Nair, Daya R. (Seminars in Speech and Language, 2025)
The study aimed to cross-linguistically adapt the Sydney Swallow Questionnaire in Malayalam (MSSQ) and to determine its psychometric properties. The objectives of our study were to document the test–retest reliability, internal consistency, and discriminant validity of MSSQ. The SSQ was translated from English to Malayalam, and was administered to 55 Malayalam-speaking participants with oropharyngeal dysphagia and 55 age- and gender-matched Malayalam speakers with normal swallowing ability. The Kolmogorov—Smirnov normality test was performed to check the normality of the data. Cronbach's alpha was used to measure the test–retest reliability. Internal consistency was measured through split-half reliability using the Spearman–Brown correlation coefficient. The discriminant validity was documented using the Mann–Whitney U-test. The Cronbach's alpha value for the total MSSQ scores was 0.99, indicating a strong positive correlation between the test and retest scores. The Spearman–Brown correlation coefficient was 0.97, indicating that the MSSQ had excellent internal consistency. Mann–Whitney U-test revealed that Group 1 participants had significantly higher MSSQ scores than Group 2 participants, exhibiting excellent discriminant validity. It was concluded that the MSSQ was a valid and reliable tool to assess the symptoms of dysphagia among Malayalam speakers.
Keywords: Sydney Swallow Questionnaire; oropharyngeal dysphagia; reliability; validity; psychometric properties